Modern T cell technologies for immunotherapy of solid tumors - M. S. Kuznetsova; Hiroshi Shiku; A. V. Karaulov; S. V. Sennikov (Медицинская иммунология, 2023)
According to the common concept of immune editing, the interaction of malignant tumor cells and immune system is a complex multifactorial process, which may result in both antitumor effector activity and development of suppressor mechanisms that promote tumor growth. Accumulation of scientific knowledge in the field of studying the antitumor immune response and tolerance has led to emergence of many research and therapeutic approaches that use different components of the immune system to combat neoplastic processes. Along with currently available approaches, there are strategies that use the potential of antigen-specific T lymphocytes, the main effectors of adaptive immunity, in order to fight malignant neoplasms which appeared more than a century ago and have built the scientific basis of cancer immunotherapy. One line of evidence of the significant antitumor potential of T cells in immunotherapeutic schemes for the cancer treatment was presented by successful therapy of hemato-oncological diseases, achieved at the end of the past decade. At the same time, however, the therapy of solid malignant neoplasms still faces significant difficulties that limit the efficiency of treatment. In this regard, the main objective of the review is to accumulate up-to-date information on the successes and limitations of T cell immunotherapy in the patients with solid tumors. To date, the phenotype and functionality of T cells is being investigated and modulated both towards enhancing antitumor cytotoxicity, increasing viability and proliferative activity of T cells, and in overcoming the immunosuppressive effect of the tumor and its tolerogenic microenvironment upon T cells, as well as ensuring targeted migration of the effector T cells to the malignant tissues. This review discusses immunotherapeutic approaches exploiting the potential of effector T lymphocytes, e.g., current clinical trials or applied therapeutic regimens for the treatment of solid malignant neoplasms. Antigen-independent approaches aimed at nonspecific enhancement of the T cell responses, i.e., therapy with recombinant cytokines and inhibition of immune checkpoint molecules. Antigendependent, or antigen-specific approaches such as adoptive T cell therapy with endogenous T lymphocytes are also discussed as well as trials on T cells with modified antigen-recognition receptor (CAR-Tcells, TCR-Tcells), like as usage of bispecific antibodies as T cell engagers. The review describes the benefits and disadvantages of these approaches in monotherapy, as well as current results and prospects for their mutual combinations.